Antagonism of aminoacid transport in primary CD4 T cells by HIV-1 Vpu. (26th February 2015) - Matheson, Nicholas; Wals, Kim; Weekes, Michael; Rapiteanu, Radu; Vigan, Raphael; Antrobus, Robin; Smith, Duncan; Neil, Stuart; Lehner, Paul
Abstract: Background: Less than 100 years since it was first transmitted to the human population HIV-1 infects more than 30 million people worldwide and causes almost 2 million AIDS-related deaths every year. Viruses manipulate cellular genes and pathways to benefit their survival, and the study of cell surface proteins downregulated by viruses has provided insights into both viral pathogenesis and crucial aspects of cell biology. We aimed to identify novel cell surface proteins targeted for downregulation by HIV-1. Methods: We combined plasma membrane enrichment through selective aminooxybiotinylation with tandem mass tag-based quantitative proteomics (plasma membrane profiling) to map expression timecourses of more than 800 plasma membrane proteins in T cells infected in vitro with HIV-1. Novel substrates of the viral accessory proteins Vpu and Nef were sought by use of deletion viruses and single gene overexpression. Findings: Our proteomic datasets defined more than 100 previously unsuspected cell surface targets of HIV-1, particularly proteins involved in T-cell activation, cell adhesion, and aminoacid transport. In addition to its known targets, Vpu was found to be necessary and sufficient for the downregulation of the aminoacid transporter TOV3. Downregulation of TOV3 was post transcriptional, mediated by the β-TrCP ubiquitin E3 ligase and occurred via an endolysosomal pathway. TOV3 was highly expressed in primary human CD4 T cells, and depletion of TOV3 by RNA interference markedly impaired the mitogenic response to CD3/CD28 stimulation. We identified alanine as an endogenous TOV3 substrate, and showed that extracellular alanine was crucial for T-cell proliferation. Interpretation: This study suggests that TOV3 downregulation is restricted to Vpu variants from the lineage of HIV-1 group M viruses giving rise to pandemic AIDS. Antagonism of alanine transport in CD4 T cells might contribute to HIV-1 pathogenesis through modulation of virus production, impairment of the adaptive immune response, or enhancement of CD4 T-cell loss. Funding: Wellcome Trust, Addenbrooke's Charitable Trust, Raymond and Beverly Sackler Foundation.